Vat photopolymerization of high molecular weight polymer latexes with pseudothermoplastic properties for recyclability - Ayestaran, Jon; de Pariza, Xabier Lopez; Vidal, Fernando; Vázquez-Martel, Clara; Pascal, Alodi; Yu, Siwei; Aguirre, Miren; Nelson, Alshakim; Leiza, Jose R.; Blasco, Eva; Long, Timothy E.; Aguirresarobe, Robert; et al. (Advanced functional materials, 2025)
Additive manufacturing (AM), or 3D printing, has rapidly advanced due to its customization, speed, and precision manufacturing. Traditional vat photopolymerization (VPP) often produces densely cross-linked, brittle, and non-reprocessable materials, contributing to plastic waste generation. To address these issues, a UV-reactive latex formulation combining water-dispersed thermoplastics with a minimal amount of photocurable water-soluble additive yielding reprocessable pseudothermoplastic materials are proposed. The selection of the water-soluble additive is crucial not only to enable the printing of high molecular weight thermoplastics with exceptional resolution and tunable properties but more importantly also to retain the properties of the initial latex-containing polymer while tackling reprocessability issues in photoprinted materials. Reprocessability is demonstrated using traditional manufacturing techniques (e.g., injection, hot-pressing) as well as extrusion 3D printing. Furthermore, optimized photocurable latex resins are suitable for two-photon 3D laser printing, enabling the miniaturization of features using the materials reported herein. This innovation opens new pathways for creating reprocessable, high-performance 3D-printed materials with on-demand properties.
Gesehen am 09.10.2025